200 Distinct Distribution Pattern of Skeletal and Neuronal-Type Sodium Channel Isoforms within the Rat Ventricle, with Focus on Neuronal Sodium Channels 1.7, 1.8 and 1.9. (6th June 2015) - Cooper, Stephanie; Jones, Sandra
Abstract : Voltage-gated sodium channels (VGSCs) generate the Na + current (INa ) responsible for the cardiac action potential upstroke largely due to the 'cardiac' isoform Nav 1.5, but with ˜20% of the upstroke and a component of a sustained sodium current, attributed to other isoforms. This sustained component has been attributed with increasing arrhythmia risk and has been the target of development for new anti-arrhythmic drugs, targeted at 'neuronal' isoforms. Distinctive distribution patterns of Nav isoforms 1.1–1.6 have been demonstrated in human atrial myocardium, 1 suggesting differing isoforms have spatially distinct roles; however little is known regarding the expression of the neuronal isoforms Nav 1.7, Nav 1.8 and Nav 1.9 in the heart. Our study has investigated the subcellular distribution patterns of VGSC alpha-subunits Nav 1.1–1.9 in the rat heart. Rats ˜300 g were sacrificed and ventricular tissue or single myocytes isolated. Immunocytochemistry showed the location of VGSCs within single cardiac myocytes or tissue sections using primary VGSCs antibodies (Alomone, Israel) bound to secondary antibodies conjugated to Alexa 488 (Molecular probes, UK), and cellular membranes labelled by wheat germ agglutinin conjugated to rhodamine (Vector, UK), viewed by confocal microscopy (Zeiss 710, Germany). The dominant cardiac isoform, Nav 1.5, was expressed at the sarcolemma membrane, intercalated disk and t-tubular membrane, whereas the skeletal muscle isoform Nav 1.4 was detected at intercalated disks as an intense punctate pattern. Nav 1.3 was not detected. 2 The neuronal-associated isoforms Nav 1.1, Nav 1.2 and Nav 1.6 positively labelled rat brain sections; whereas in cardiac tissue Nav 1.1 showed faint punctate labelling, 1 Nav 1.2 showed t-tubular staining, and Nav 1.6 showed intercalated disk, faint t-tubular expression as well as nuclear labelling. As reported by others, 3, 4 sensory neurons from rat dorsal root ganglia labelled positive for Nav 1.7, 1.8 and 1.9. In heart tissue and cells; Nav 1.8 protein expression was a striated pattern throughout the cell, whereas Nav 1.9 protein was found at the intercalated disks, t-tubules and nuclei. Nav 1.7 expression was not observed in cardiac tissue or myocytes. We conclude that in addition to Nav1.5, other sodium channels are expressed in the rat heart (Nav 1.1, Nav 1.2, Nav 1.4, Nav 1.6, Nav 1.7 and Nav 1.8) and may play distinct roles in the cardiac action potential, however these are yet undetermined. References: Westenbroek K, Lange M, Wischmeyer R, Muck B, Catterall E, Maier S. JMCC 2013;61:133–41 Cardiovascular Disease Statistics 2014, The BHF Annual Statistics. 2014. Alsheikh-Ali AA et al . Annals of Internal Medicine . 2010. Caro CG et al . Nature . 1969.